Prognosis and outcome of stem cell transplantation for mantle cell lymphoma. Issue 4 (August 2015) - Cheminant, Morgane; Robinson, Stephen; Ribrag, Vincent; Le Gouill, Steven; Suarez, Felipe; Delarue, Richard; Hermine, Olivier
Abstract : Although the overall survival has improved significantly in mantle cell lymphoma, relapsed disease remains a challenge. It has been demonstrated that high-dose cytarabine- and rituximab-containing regimens in induction improve response rate before autologous stem cell transplantation. This therapeutic strategy performed in first-line therapy improves significantly both progression-free survival and overall survival and has emerged as a new standard of care in younger patients. The role of allogeneic stem cell transplantation and its place in the treatment algorithm is not fully established, but may be a curative strategy. However, new therapeutic strategies such as maintenance/preemptive therapy or novel targeted therapies may challenge and change the indications of stem cell transplantation. This review will discuss the role of stem cell transplantation in mantle cell lymphoma and how emerging treatment strategies and novel therapies may challenge the current paradigms of therapy.